Comprehensive analysis of grazing intensity impacts on different types of grassland in Xinjiang, China: a meta-analysis - Zheng, Yu; Yao, Huifang; Chao, Kairui; Ma, Xiuzhi; Ma, Yanan (Frontiers in Plant Science, 2025)
Grazing is the primary use of grassland in Xinjiang and plays a key role in the grassland ecosystem. Grazing intensity has a profound impact on the healthy development of grassland. To date, we lack a comprehensive understanding of the overall response of the main types of grassland in Xinjiang to different intensities of grazing. Based on 73 peer-reviewed studies, we conducted a meta-analysis of the response of soil properties and community vegetation characteristics to grazing intensity in five main types of grassland in Xinjiang. The results showed the following: (1) Grazing reduced the soil total carbon (TC) and total potassium (TK) of grassland soil in Xinjiang and increased the content of available phosphorus (AP) in soil. Moderate grazing reduced the soil TC and increased the total nitrogen (TN). Heavy grazing significantly reduced soil organic carbon (SOC) and density (P < 0.05). (2) The SOC of temperate meadow steppe decreased significantly under moderate and heavy grazing, and the three grazing intensities significantly reduced the biomass carbon storage of living plants and litter carbon storage (P < 0.05). (3) Soil pH and AP in temperate steppe increased significantly under light grazing, and soil bulk density (BD) and total phosphorus (TP) increased significantly under heavy grazing (P < 0.05). (4) The soil water content (SWC) and pH of temperate desert steppe decreased significantly under moderate grazing. Heavy grazing increased soil BD. Light grazing increased pH and available nitrogen (AN), and decreased soil TN, TP, and TK (P < 0.05). (5) The soil organic matter of mountain meadow increased significantly under light and moderate grazing. Light grazing reduced aboveground and underground standing crop and root-shoot ratio, and increased carbon storage (P < 0.05). (6) Under heavy grazing, SWC and total biomass in alpine meadow decreased significantly, whereas pH, AN, and AP increased significantly. Soil BD decreased significantly under light and moderate grazing (P < 0.05). The structural equation model showed that the increase in grazing intensity would reduce the vegetation coverage of the community and thus would reduce species diversity. The increase in grazing intensity also had a significant negative effect on aboveground biomass and soil quality.